Juridical Issues and the Application of Criminal Law Principles in Content-Related Offenses under the Electronic Information and Transactions Law - Muhammad Tri Apriyansyah Idris; Adi Mansar (PT FORMOSA CENDEKIA GLOBAL, 2026)
The Electronic Information and Transactions Law (ITE Law) is the primary legal framework in Indonesia, regulating various acts in the digital space as non-conventional crimes. This study aims to analyze the effectiveness and challenges of cybercrime law enforcement, with a particular focus on content crimes. Using a juridical-normative research method, this study examines the implementation of the principle of criminal responsibility and the validity of electronic evidence in judicial practice. The results indicate that while the ITE Law is quite effective in addressing technical crimes such as hacking, its effectiveness in combating content crimes remains limited due to the problem of